2010
DOI: 10.1161/circresaha.109.206615
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption Enhances High-Density Lipoprotein-Mediated Cholesterol Efflux in Macrophages

Abstract: Rationale: Association of habitual coffee consumption with coronary heart disease morbidity and mortality has not been established. We hypothesized that coffee may enhance reverse cholesterol transport (RCT) as the antiatherogenic properties of high-density lipoprotein (HDL). Objective: This study was to investigate whether the phenolic acids of coffee and coffee regulates RCT from macrophages in vitro, ex vivo and in vivo. Methods and Results: Caffeic acid and ferulic acid, the major phenolic acids of coffee,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 44 publications
5
68
1
2
Order By: Relevance
“…Anthocyanins, a large group of naturally phe-nolic compounds abundant in plants, enhanced ABCA1 expression by stimulating PPAR ␥ /LXR pathways, thus resulting in increased cholesterol efflux from macrophages. We recently observed that coffee's phenolic acids, caffeic/ferulic acids, induced ABCG1 and scavenger receptor class B, type I (SR-BI) expression, which is also involved in HDL-mediated cholesterol efflux, leading to increased HDL-mediated cholesterol efflux from macrophages ( 8 ). Additionally, in line with the in vitro finding, ferulic acid was found to promote overall RCT in vivo in mice.…”
mentioning
confidence: 61%
“…Anthocyanins, a large group of naturally phe-nolic compounds abundant in plants, enhanced ABCA1 expression by stimulating PPAR ␥ /LXR pathways, thus resulting in increased cholesterol efflux from macrophages. We recently observed that coffee's phenolic acids, caffeic/ferulic acids, induced ABCG1 and scavenger receptor class B, type I (SR-BI) expression, which is also involved in HDL-mediated cholesterol efflux, leading to increased HDL-mediated cholesterol efflux from macrophages ( 8 ). Additionally, in line with the in vitro finding, ferulic acid was found to promote overall RCT in vivo in mice.…”
mentioning
confidence: 61%
“…3 Hcholesterol-labeled and acLDL-loaded RAW264.7 cells (typically 5.0 10 6 cells containing 7.5 10 6 counts per minute [cpm] in 0.5 mL RPMI 1640) were injected intraperitoneally as described previously [21][22][23] . Blood samples were obtained from the tail vein under anesthesia prior to administration of the SUAs and at 24 and 48 h after injection of RAW264.7 cells.…”
Section: Isolation Of Mouse Peritoneal Macrophages and Livers After Omentioning
confidence: 99%
“…Liver lipids were extracted as described previously [21][22][23] . Briefly, a 50 mg piece of tissue was homogenized in water, and lipids were extracted with a 2:1 (vol/vol) mixture of chloroform/methanol.…”
Section: Liver Bile and Fecal Analysesmentioning
confidence: 99%
“…This study failed to show promoting effects of homoplantaginin and hispidulin, on ABCA1 expression. However, caffeic acid, one of Salvia plebeia constituents, enhanced cholesterol efflux from THP-1 macrophages mediated by HDL, and induced expression of ABCG1 and SR-BI but not ABCA1 (26). Thus, other unknown components appeared to be responsibe for increasing cholesterol efflux and HDL formation by SWE.…”
Section: Discussionmentioning
confidence: 93%